Failure Analysis and Maintenance Strategy of Pneumatic System Components in Rail-Road Loader KGT/V - M Karil Samba Athari; Ocky Soelistyo Pribadi; Erni Basri; Fadli Rozaq; Probo Hardini (Politeknik Perkeretaapian Indonesia Madiun, 2026)
The Rail-Road Loader KGT/V is a multifunctional heavy equipment used for railway track maintenance and repair, with a pneumatic system playing a vital role in braking and stabilization mechanisms. This study aims to analyze the failure of pneumatic system components in the Rail-Road Loader KGT/V unit, primarily caused by air moisture and condensation, and to formulate solutions for improving system reliability. The research applies several methods, including downtime analysis, Mean Time Between Failures (MTBF), Mean Time to Repair (MTTR), Failure Modes and Effects Analysis (FMEA), Reliability Centered Maintenance (RCM), and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). Results indicate that high humidity at the operational sites triggers failures in key components such as seals, valves, and pressure sensors, leading to increased equipment downtime. The installation of an air dryer is identified as the most effective technical solution to mitigate condensation issues. According to the TOPSIS analysis, implementing an air dryer ranks highest among proposed alternatives. This study recommends installing air dryers and developing a systematic maintenance procedure to enhance the reliability of the pneumatic system and ensure safer operational performance of the Rail-Road Loader KGT/V.